2010
DOI: 10.5301/jabb.2010.6104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Freeze-Drying on the Mechanical, Physical and Morphological Properties of Glutaraldehyde-Treated Bovine Pericardium: Evaluation of Freeze-Dried Treated Bovine Pericardium Properties

Abstract: Purpose: Biomaterials have been widely used in the field of regenerative medicine. Bovine pericardium tissue has been successfully used as a bioprosthetic material in manufacturing heart valves, but studies concerning the tissue are ongoing in order to improve its storage, preservation and transportation. this article provides an overview of the characteristics of bovine pericardium tissue chemically treated after the freeze-drying process. these characteristics are essential to evaluate the changes or damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
2
2
0
1
Order By: Relevance
“…Normal histologic characteristics in LyoPA grafts after rehydration revealed that lyophilization, by freezing water and removing ice by sublimation, maintained global morphologic characteristics and protein activity. This finding is consistent with that described by other authors who studied the effect of lyophilization on various tissues used as bioprostheses ( 3 , 7 , 8 , 15 , 20 , 33 ). Histologic changes observed in group II were probably because lyophilization maintained the matrix structure and graft walls, as several authors who have used lyophilized prostheses (treated and untreated with different chemicals) have reported ( 3 , 7 , 8 , 16 , 34 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Normal histologic characteristics in LyoPA grafts after rehydration revealed that lyophilization, by freezing water and removing ice by sublimation, maintained global morphologic characteristics and protein activity. This finding is consistent with that described by other authors who studied the effect of lyophilization on various tissues used as bioprostheses ( 3 , 7 , 8 , 15 , 20 , 33 ). Histologic changes observed in group II were probably because lyophilization maintained the matrix structure and graft walls, as several authors who have used lyophilized prostheses (treated and untreated with different chemicals) have reported ( 3 , 7 , 8 , 16 , 34 ).…”
Section: Discussionsupporting
confidence: 93%
“…They showed high hemostatic capacity and excellent hemodynamic response in the immediate postoperative period, and allowed easy passage of the suture because mechanical properties were retained. These findings are consistent with those described by Taniguchi et al ( 3 ), Borgognoni et al ( 15 ), and Flameng et al ( 16 ) with regard to the properties of a lyophilized bovine pericardial bioprostheses. Findings for CryoPA grafts were similar to those described by Gómez-Caro et al ( 6 ), who studied vessel reconstruction after excision of thoracic malignancies using arterial cryopreserved allografts.…”
Section: Discussionsupporting
confidence: 93%
“…The present study utilized a modified version of the previously reported protocol and confirmed the lack of pores in the FD BDP scaffolds and the preservation of the overall scaffold architecture. Freeze-drying without a lyoprotectant has been shown to result in significant structural and mechanical damages to the tissue [38,39,42,77].…”
Section: Discussionmentioning
confidence: 99%
“…Freeze‐drying of biological tissue, as bovine pericardium (BP), allows dry storage and gamma ray sterilization without changing in mechanical, physical, and morphological properties . Besides that, the lyophilization process of BP before chemical treatments may be an alternative to the conventional calcification prevention methods without affecting the hydration .…”
Section: Discussionmentioning
confidence: 99%